2020
DOI: 10.1001/jamaoncol.2020.3960
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Immune-Related Adverse Events After Immune Checkpoint Inhibitor Rechallenge—Reply

Abstract: To the Editor Recently, with the increasing research on immunerelated adverse events (irAEs) in patients treated with immune checkpoint inhibitors (ICIs), recurrence of irAEs after ICI rechallenge has deserved more attention. In their cohort study, Dolladille and colleagues 1 retrospectively assessed safety in patients with cancer who resumed therapy with the same ICIs and found that ICI rechallenge was associated with a recurrence of the same irAEs in one-quarter to one-third of the cases. However, there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In contrast with prior findings suggesting that irAE recurrences tend to be easily managed, we found that 40% of irAE recurrences were high-grade, and nearly half occurred despite not being re-challenged with ICI therapy. [33][34][35][36][37] Finally, a considerable proportion of patients required subspecialty referral or hospitalization for irAE management. Our study highlights that irAE are clinically impactful and may contribute to further healthcare utilization, although this needs to be studied further.…”
Section: Clinical Impact Of Iraementioning
confidence: 99%
“…In contrast with prior findings suggesting that irAE recurrences tend to be easily managed, we found that 40% of irAE recurrences were high-grade, and nearly half occurred despite not being re-challenged with ICI therapy. [33][34][35][36][37] Finally, a considerable proportion of patients required subspecialty referral or hospitalization for irAE management. Our study highlights that irAE are clinically impactful and may contribute to further healthcare utilization, although this needs to be studied further.…”
Section: Clinical Impact Of Iraementioning
confidence: 99%